2022
DOI: 10.1002/jper.21-0419
|View full text |Cite
|
Sign up to set email alerts
|

Pro‐inflammatory profiles in cardiovascular disease patients with peri‐implantitis

Abstract: Background To investigate the pro‐inflammatory cytokine profiles in patients with or without cardiovascular disease (CVD) and with or without peri‐implantitis. Methods Serum, peri‐implant crevicular fluid (PICF), and gingival crevicular fluid (GCF) were collected from patients with (n = 82) or without CVD (n = 46) at the most severe peri‐implantitis site including sites with periodontitis. A panel of proinflammatory molecules including high‐sensitivity C‐reactive protein (hsCRP), fibrinogen, interleukin‐1 beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Furthermore, the levels of IL-1β and TNF-α in lung tissues from mice with sepsis were markedly decreased by LMT-28 [28]. As inflammatory biomarkers, the variations of IL-1β, IL-6, and TNF-α are the most commonly studied functional polymorphisms for periimplantitis and peri-implant bone loss [18,33,34]. Thus, the multiple effects of LMT-28 are anticipated to be appropriate for tissue repair in many bone-related diseases and organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the levels of IL-1β and TNF-α in lung tissues from mice with sepsis were markedly decreased by LMT-28 [28]. As inflammatory biomarkers, the variations of IL-1β, IL-6, and TNF-α are the most commonly studied functional polymorphisms for periimplantitis and peri-implant bone loss [18,33,34]. Thus, the multiple effects of LMT-28 are anticipated to be appropriate for tissue repair in many bone-related diseases and organs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the combination of IL-6/IL-6R and GP130 in osteoblasts, which subsequently activated the JAK signaling pathway and preferentially induced tyrosine phosphorylation of STAT3, also correlated with RANKL levels. The JAK2/STAT3 signal transduction pathway is one of the main pathways through which IL-6 exerts its biological roles and plays a critical part in inflammatory bone disease [33]. To study the role of the JAK2/STAT3 signaling pathway in the expression of RANKL, we used LPS, AGEs, LMT-28, and the JAK2 inhibitor baricitinib to treat osteoblasts, and we observed that LPS and AGEs stimulated the expression of p-STAT3, p-JAK2, and RANKL, which were inhibited by baricitinib and LMT-28.…”
Section: Discussionmentioning
confidence: 99%
“…Hom-Lay Wang's studies showed that 64.6% of peri-implantitis was found in CVD patients, while only 56.5% of peri-implantitis was found in the controls ( 65 ). Moreover, IL-1β and TNF-α were significantly higher in CVD patients, which were significant markers for peri-implantitis ( 66 ). Inflammation plays a crucial role in the pathogenesis of atherosclerosis, the underlying cause of many cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In both abutment groups, a significant decrease in the expression of CRP, IL-6, MIP - 1α, osteopontin, and osteoactivin in PICF during the 6-month observation period was measured; this suggests a reduction of the inflammation process. While CRP is known as a marker for systemic inflammation, it has also been detected in PICF at peri-implantitis sites [ 18 ]. As a classical pro-inflammatory cytokine, IL-6 has been used to assess peri-implant inflammation in PICF [ 19 ].…”
Section: Discussionmentioning
confidence: 99%